A Case Report: Pancytopenia Secondary to Urosepsis and Acute Kidney Injury in a 23-Year-Old Female with Intellectual Disability - T M, Karthikeya; Theja, Pranav; Anand, N N; Balaji N, Balaji N; VinodKrishna, Gopalagari (Journal of Neonatal Surgery, 2025)
A 23-year-old female with a history of intellectual disability presented with fever, altered mental status, and reduced urine output. Laboratory investigations revealed pancytopenia and acute kidney injury (AKI). Urine culture was positive for Escherichia coli, confirming urosepsis as the underlying etiology. The patient was managed with broad-spectrum antibiotics, intravenous fluids, and supportive care, leading to resolution of AKI and pancytopenia. This case highlights the importance of early recognition and management of urosepsis in patients with neurodevelopmental disorders, who may have atypical presentations.